YouTube TM Videos as a Source of Information on Clear Retainers - Ramya Vijeta Jathanna1 , Krishnaraj K.K2 , P.N. Roopalekha Jathanna3 , Vinod Rakesh Jathanna4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Internet is one of the most important information sources in dental field to obtain informationregarding treatment procedures. The content and quality of information about clear retainers available onYouTube is not known. The aim of the study was to analyze the source and quality of information about clearretainers on YouTube.Methods: The search keywords were “clear retainers”. The first 100 results were arranged in decreasing orderof “relevance” using default YouTube algorithm. Two orthodontists independently viewed and analyzed thevideos for video content using customized 10-point Likert scale and video information and quality index(VIQI) to determine the quality of the videos.Results: Out of 100 videos screened, 48 videos met the inclusion criteria. The inter investigator results weresimilar in evaluating video content and the findings was not significant except for comparison by investigatorII (p=0.006). For VIQI, internal consistency showed good reliability of Cronbach’s Alpha .855. Most ofthe videos were uploaded by layperson (64.6%) rather than dental professionals (29.2%). Instructions onretainer hygiene was the most commonly covered topic (64.6%), followed by handling the retainer (60.4%).The least mentioned content was the procedure of making the clear retainer (19.8%).Conclusion: The results of the study sheds light on the inadequacies in the content of the YouTube videoson clear retainers and also points out the underrepresentation of videos uploaded by dental professionals andorthodontists. The study suggests that YouTube is currently not an appropriate source of information on clearretainers. Dental professionals and academic institutions hold a responsibility for improving the content ofYouTube about clear retainers and directing the patients to professional online sites for reliable information.